Feature Level Fusion of Face and voice Biometrics systems using Artificial Neural Network for personal recognition - Dalila, Cherifi; Omar Badis, El Affifi; Saddek, Boushaba; Amine, Nait-Ali (Informatica, 2020)
Lately, human recognition and identification has acquired much more attention than it had before, due to the fact that computer science nowadays is offering lots of alternatives to solve this problem, aiming to achieve the best security levels. One way is to fuse different modalities as face, voice, fingerprint and other biometric identifiers. The topics of computer vision and machine learning have recently become the state-of-the-art techniques when it comes to solving problems that involve huge amounts of data. One emerging concept is Artificial Neural networks. In this work, we have used both human face and voice to design a Multibiometric recognition system, the fusion is done at the feature level with three different schemes namely, concatenation of pre-normalized features, merging normalized features and multiplication of features extracted from faces and voices. The classification is performed by the means of an Artificial Neural Network. The system performances are to be assessed and compared with the K-nearest-neighbor classifier as well as recent studies done on the subject. An analysis of the results is carried out on the basis Recognition Rates and Equal Error Rates. Index Terms: Bioinformatiscs, Face, voice, Multibiometric recognition system, fusion at feature level, Artificial Neural Network(ANN).